Multicultural Learning Model of PAUD in Coastal Areas - Hadi Machmud; Nur Alim (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2018)
Early Childhood Education in coastal areas is different from PAUD on land, this diversity requires a learning model that can bond togetherness indifference, a learning model that instills values and norms in a learning process. This article offers a learning model that fits the characteristics of early childhood in the Pesisir city of Kendari. This model can bring innovative ideas that demand the creativity of teachers and high school authorities involved in making their own decisions, planning, and implementation. It takes a leap to be able to catch up due to the neglect of local wisdom that has experienced many obstacles in the learning process at school.